The Motivation of Temporary Agency Workers: An Empirical Analysis - Christian Grund; Axel Minten; Nevena Toporova (Institute of Labor Economics (IZA), 2017)
We are investigating the relationship between individual and job-related characteristics and the motivation of temporary agency workers. To do so, we are using a unique dataset from one of Germany's largest temporary work agencies. For 3,000 temporary agency workers, a subjective motivation appraisal is provided by the respective direct manager within the hiring company. It is possible to observe a positive relationship between the decision on transition to regular employment and the motivation of temporary agency workers. Women in temporary agency work demonstrate a higher degree of motivation than men. However, in the case of men a clearer correlation can be observed between project duration and motivation. A change of hiring company with follow-up projects has a negative effect on the temporary agency worker's motivation.
Keywords: J5; J81; M5; 330; temporary agency work; atypical employment relation; empirical study; motivation; work morale